2017
DOI: 10.1089/neu.2017.5076
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injury in a Community-Based Cohort of Homeless and Vulnerably Housed Individuals

Abstract: We characterized traumatic brain injury (TBI) and studied its associations with mental and physical health in a community cohort of homeless and vulnerably housed individuals. Detailed mental and physical health structured interviews, neuropsychological testing, and multimodal magnetic resonance imaging (MRI) were performed on 283 participants. Two TBI participant groups were defined for primary analyses: those with a self-reported history of TBI and those with MRI confirmation of TBI. By self-report, 174 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Traumatic brain injury in our sample is associated with abnormalities of neural connectivity and cross-sectional cognitive impairment, 37 and is now observed to be associated with steeper memory decline. A study of nearly 2.8 million people from Denmark found an increased risk of all-cause dementia in people with a history of traumatic brain injury.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Traumatic brain injury in our sample is associated with abnormalities of neural connectivity and cross-sectional cognitive impairment, 37 and is now observed to be associated with steeper memory decline. A study of nearly 2.8 million people from Denmark found an increased risk of all-cause dementia in people with a history of traumatic brain injury.…”
Section: Discussionmentioning
confidence: 67%
“…Heavy alcohol consumption with increasing age is linked with greater impairment in learning, memory and motor functions, but not attention and executive functioning, and is considered to reflect a dual premature-accelerated model of cognitive ageing. 36 Traumatic brain injury in our sample is associated with abnormalities of neural connectivity and cross-sectional cognitive impairment, 37 and is now observed to be associated with steeper memory decline. A study of nearly 2.8 million people from Denmark found an increased risk of all-cause dementia in people with a history of traumatic brain injury.…”
Section: Individual-level Risk Factorsmentioning
confidence: 78%
“…Proximal traumatic events may also exacerbate risk, and together, these risk factors may have additive or synergistic effects on expression of psychosis in adulthood [ 28 , 29 ]. Among precariously housed individuals, traumatic brain injury (TBI) is reported in a meta-analysis to have a prevalence of over 50%, with over 20% being of at least moderate severity [ 25 , 26 , 30 ]. TBI is associated with paranoid delusions and hallucinations, even years after the injury [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…This speculation is supported by the fact that only a minority of people who enter shelters in NYC have previously accessed available homelessness prevention services . Prior research has suggested high rates of traumatic brain injury and cognitive impairment among people who are homeless, which may have also been somewhat contributory to our findings, although we did exclude patients who were not able to understand the study informed consent process.…”
Section: Discussionmentioning
confidence: 99%